2019
DOI: 10.1161/strokeaha.119.025914
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Blood-Brain Barrier Disruption Post-Endovascular Therapy and Multiple Thrombectomy Passes in Acute Ischemic Stroke Patients

Abstract: Background and Purpose— The high prevalence of hyperintense acute reperfusion marker (HARM) seen after endovascular therapy is suggestive of blood-brain barrier disruption and hemorrhage risk and may be attributable to multiple thrombectomy passes needed to achieve recanalization. Methods— Patients with acute stroke were included if they were screened from January 2015 through February 2019, received an acute ischemic stroke diagnosis involving the ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 15 publications
3
31
0
Order By: Relevance
“…2 ). Most studies were performed in cases with ischemic stroke, transient ischemic attack (TIA), and/or intracerebral hemorrhage (ICH) (n = 20) ( Villringer, 2017 , Ostwaldt, 2015 , Ostwaldt, 2014 , Warach and Latour, 2004 , Latour et al, 2004 , Choi, 2017 , Dechambre, 2000 , Forster et al, 2016 , Gupta, 2017 , Henning et al, 2008 , Hjort, 2008 , Kim, 2005 , Luby, 2019 , Nadareishvili, 2018 , Lee, 2015 , Lee, 2016 , Lee, 2018 , Rozanski, 2010 , Kidwell et al, 2011 , Jolink, et al, 2019 , Barr, 2010 ). Six studies described patients who underwent cardiovascular or intracranial vascular surgery ( Cho, 2014 , Ogami et al, 2011 , Wilkinson, 2000 , Li, 2018 , Suthiphosuwan et al, 2018 , Merino, 2013 ), nine studies patients with multiple sclerosis (MS) (one of these included stroke cases as a positive control ( Eisele, 2015 ) ( Eisele, 2015 , Absinta, 2015 , Bergsland, 2019 , Harrison, 2017 , Jonas et al, 2018 , Zivadinov, 2017 , Zivadinov, 2018 , Zurawski, 2020 , Ighani, 2020 ), four studies patients with meningitis ( Ahmad et al, 2015 , Alonso, 2015 , Fukuoka, 2010 , Splendiani, 2005 ), two studies reported on memory clinic patients and normal aging ( Freeze, 2017 , Freeze et al, 2019 ), one study on Susac syndrome and MS ( Coulette, 2019 ), one study on familial amyloid polyneuropathy ( Hirai, 2005 ), and one study included a mix of diseases, which were presented as follows: inflammatory and immune-mediated neurologic diseases (neuromyelitis optica spectrum disorder, immune-mediated encephalitis, immune-mediated cerebellar ataxia, systemic inflammatory diseases with white matter MRI abnormalities not suggestive for MS and Susac syndrome), noninflammatory neurologic diseases (small vessel disease, migraine, neurodegenerative diseases, compressive myelopathy), human T-lymphotropic virus (HTLV) infection,...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2 ). Most studies were performed in cases with ischemic stroke, transient ischemic attack (TIA), and/or intracerebral hemorrhage (ICH) (n = 20) ( Villringer, 2017 , Ostwaldt, 2015 , Ostwaldt, 2014 , Warach and Latour, 2004 , Latour et al, 2004 , Choi, 2017 , Dechambre, 2000 , Forster et al, 2016 , Gupta, 2017 , Henning et al, 2008 , Hjort, 2008 , Kim, 2005 , Luby, 2019 , Nadareishvili, 2018 , Lee, 2015 , Lee, 2016 , Lee, 2018 , Rozanski, 2010 , Kidwell et al, 2011 , Jolink, et al, 2019 , Barr, 2010 ). Six studies described patients who underwent cardiovascular or intracranial vascular surgery ( Cho, 2014 , Ogami et al, 2011 , Wilkinson, 2000 , Li, 2018 , Suthiphosuwan et al, 2018 , Merino, 2013 ), nine studies patients with multiple sclerosis (MS) (one of these included stroke cases as a positive control ( Eisele, 2015 ) ( Eisele, 2015 , Absinta, 2015 , Bergsland, 2019 , Harrison, 2017 , Jonas et al, 2018 , Zivadinov, 2017 , Zivadinov, 2018 , Zurawski, 2020 , Ighani, 2020 ), four studies patients with meningitis ( Ahmad et al, 2015 , Alonso, 2015 , Fukuoka, 2010 , Splendiani, 2005 ), two studies reported on memory clinic patients and normal aging ( Freeze, 2017 , Freeze et al, 2019 ), one study on Susac syndrome and MS ( Coulette, 2019 ), one study on familial amyloid polyneuropathy ( Hirai, 2005 ), and one study included a mix of diseases, which were presented as follows: inflammatory and immune-mediated neurologic diseases (neuromyelitis optica spectrum disorder, immune-mediated encephalitis, immune-mediated cerebellar ataxia, systemic inflammatory diseases with white matter MRI abnormalities not suggestive for MS and Susac syndrome), noninflammatory neurologic diseases (small vessel disease, migraine, neurodegenerative diseases, compressive myelopathy), human T-lymphotropic virus (HTLV) infection,...…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies assessed CSF enhancement in cases with stroke ( supplemental table e-2 ). Fourteen studies examined acute ischemic stroke, including nine studies with non-selective and non-overlapping study samples with a total of 1148 cases and a pooled mean age of 70 years ( Ostwaldt, 2015 , Warach and Latour, 2004 , Latour et al, 2004 , Choi, 2017 , Forster et al, 2016 , Gupta, 2017 , Hjort, 2008 , Kim, 2005 , Luby, 2019 , Nadareishvili, 2018 ). The reported prevalence of CSF enhancement in these studies ranged from 12% to 65%, with a pooled prevalence estimate of 27% (95% CI 25–30).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study ( 123 ) found BBB disruption evaluated by non-contrast CT scan within 3 h of the procedure and defined as parenchymal hyperdensity on CT scan (including both blood and contrast medium), occurring in 61% of patients. Multiple thrombectomy passes have also been independently associated with a significant increase in BBB disruption as evaluated by hyperintense acute reperfusion marker (HARM) which is a hyperintensity on T2-weighted fluid-attenuated inversion recovery (FLAIR) MRI following an injection of gadolinium-based contrast agent ( 149 ). An interesting question raised by Renú et al ( 150 ) regarding such an imagological finding is whether this is attributable to MT-induced damage to BBB at a microcirculatory level or by direct damage to the proximal vessel wall where the MT device is deployed.…”
Section: Hemorrhagic Transformation: the Role Of Bbb Permeabilitymentioning
confidence: 99%